Adobe Flash Professional CC 2014 release - Chun, Russell (Classroom in a book, 2015)
The fastest, easiest, most comprehensive way to learn Flash Professional CC (2014 release) Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program does-an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe Flash Professional CC Classroom in a Book contains 10 lessons that cover the basics, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. In addition to learning the key elements of the Flash Professional interface, this completely revised CC (2014 release) edition covers new features, including the Variable Width stroke tool, the new Motion Editor panel, and improved export to Web Standards formats like HTML5 and SVG.